ANALISIS PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA PT. EAST WEST SEED INDONESIA DALAM MEMPERTAHANKAN DAYA SAING - Rafa Tartila; Ratih Purbasari; Herwan Abdul Muhyi (JURNAL LENTERA BISNIS, 2024)
This research aims to find out what factors can influence the results of use and also the implementation of CRM. The data to be obtained from informants was selected using purposive sampling techniques and using qualitative methods. The results of this research indicate that in implementing Customer Relationship Management there are obstacles or obstacles that occur in the dimensions of people, processes and technology at PT. East West Seed Indonesia. Based on the SWOT analysis results, it can be seen based on the quadrants at PT. East West Seed Indonesia is in Quadrant I (Progressive) which can be interpreted as PT. East West Seed Indonesia has good strengths which can then be utilized as an opportunity to encourage company progress.